Assessing the use of contraceptives by female undergraduate students in a selected higher educational institution in Gauteng - Maria H. Coetzee; Roinah N. Ngunyulu (AOSIS, 2015)
Background: Unplanned pregnancies amongst students at higher education institutions are a major concern worldwide, including South Africa. Apart from various social and psychological challenges, unplanned pregnancies affect students' objectives of achieving academic success. Research undertaken in the United States of America (USA) indicates that around 80% of female students in institutions of higher education between ages 18 and 24 are sexually active. Objectives: To assess and describe the use of contraceptives by undergraduate female students in a selected higher educational institution in Gauteng. Method: A cross-sectional, descriptive, quantitative design was used. A total of 400 female undergraduate students were requested to respond to a self-administered questionnaire. Stratified random sampling was used to select the participants. They were selected systematically from two campuses. Data were entered using an excel sheet at the Department of Statistics, and analysed using the Statistical Analysis Software programme, (SAS version 9.3), of the Department of Statistics' higher educational institutions. Results: A total of 74%females indicated they were sexually active, 79%of whom reported using contraceptives. The most common used methods were oral contraceptives at 38%, and 25% for male condoms. The most commonly known methods were condoms at 84%, and the oral contraceptive at 68%. The knowledge of condom use to prevent sexually transmitted diseases was high at 91%. Conclusion: Inadequate knowledge and awareness on some contraceptive methods was found. Thus, educational programmes to increase students' knowledge on the use of all contraceptive methods are urgently needed